Cost–effectiveness analysis comparing degarelix with leuprolide in hormonal therapy for patients with locally advanced prostate cancer. (April 2013) - Hatoum, Hind T; Crawford, E David; Nielsen, Sandy Kildegaard; Lin, Swu-Jane; Marshall, Dennis C
Degarelix, approved in the USA in 2008, is a gonadotropin-releasing hormone antagonist, representing one of the latest additions to androgen deprivation therapy (ADT). ADT is used as first-line therapy for locally advanced or metastatic prostate cancer with the aim to reduce testosterone to castrate levels. Like other gonadotropin-releasing hormone-antagonists, degarelix treatment results in rapid decrease in luteinizing hormone, follicle-stimulating hormone and testosterone levels without the associated risk of flare. Using one registration trial for degarelix with leuprolide as the active control, a cost–effectiveness analysis with a Markov model and a 20-year time horizon found the incremental cost–effectiveness ratio for degarelix to be US245/quality-adjusted life years. Degarelix provides a cost-effective treatment for ADT among patients with locally advanced prostate cancer.